MODELING THE PROCESS OF DEVELOPING THE METHODOLOGICAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS FOR TEACHING EDUCATIONAL DISCIPLINES IN A FOREIGN LANGUAGE - Raisa Martynova; Aryna Frumkina (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article presents the problem of modeling the process of developing the methodological competence of future primary school teachers for teaching educational disciplines in a foreign language. The notion “methodological competence of future primary school teachers” is defined. It is determined as the ability to master a methodological apparatus for presenting and activating basic knowledge in a particular discipline, and, concerning our work, it also includes the transfer of this knowledge to students in a foreign language. The process of developing methodological competence of future primary school teachers for teaching educational disciplines in a foreign language is modeled. It is based on the concept of procedural integration of two different subjects, one of which is a foreign language. This process provides simultaneous learning of different kinds of material. On the one hand, this material is related to learning the major subject, on the other hand, to learning a foreign language meaning expressing the essence of this major subject. The step-by-step model of developing the methodological competence of future primary school teachers for teaching educational disciplines in a foreign language is presented. The model covers the following links: stages of pedagogical process (1st stage – contour and art on the basis of imitation and speech, 2nd stage – subject and art on the basis of conscious speech, 3rd stage – creation and art on the basis of creative speech), educational objectives, elements of the subject, components of the content of education, methods and means of learning, as well as the control of learning outcomes. The first stage of developing the methodological competence of future primary school teachers for teaching fine arts in a foreign language is described in detail. It presents systematic and gradual growth of both major subject and linguistic knowledge and skills. This is manifested in the fact that learning each subsequent subject action involves the performance of previous actions, thus preventing pupils from forgetting the material under study. At the same time, with the development of subject and linguistic skills of different levels of complexity, the foreign language educational activity of the teacher also gradually expands, which leads to the increase in the subject and foreign language abilities of pupils.